2005
DOI: 10.1038/sj.jea.7500444
|View full text |Cite
|
Sign up to set email alerts
|

Validation of self-reported proximity to agricultural crops in a case–control study of neural tube defects

Abstract: Self-reported perinatal exposures to chemicals or pollutant sources in case-control studies of birth defects may be inaccurate due to misreporting among mothers. In a case-control study of neural tube defects delivered in California in 1987-1988, mothers of case and control infants were asked whether they lived within 0.25 mile (400 m) of agricultural crops. Responses were compared against a gold standard derived from historical agricultural land-use survey maps. The odds ratio for self-reported proximity to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…Nevertheless, non‐differential misclassification would have biased our effect estimates towards the null. Third, we cannot rule out recall bias, particularly for exposure to pesticide applications on farms or businesses near the home,47 as our analyses relied on maternally‐reported pesticide use. However, we have no evidence to believe that mothers’ report would have varied by timing or amount of exposure or by child sex.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, non‐differential misclassification would have biased our effect estimates towards the null. Third, we cannot rule out recall bias, particularly for exposure to pesticide applications on farms or businesses near the home,47 as our analyses relied on maternally‐reported pesticide use. However, we have no evidence to believe that mothers’ report would have varied by timing or amount of exposure or by child sex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in order to compare our results directly with the validation analysis of Rull et al (2006), the five categories were collapsed into two categories F r1/4 mile from farmland and 41/4 mile from farmland. Studies have shown pesticide drift from 300 m to over 1 km depending on the type of application and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown pesticide drift from 300 m to over 1 km depending on the type of application and environmental conditions. The 1/4 mile threshold was chosen because this was the closest intermediate distance presented to our participants for the range of drift from pesticides, and this approximate distance has also been used in other studies (Ward et al, 2000;Rull et al, 2006). Sensitivity, specificity, and percentage matching were calculated and compared between 1978 and 2001, and between cases and controls using Fisher's exact test and twotailed P-values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations